2x + y = 42
x - y = -3
2x + y = 42
y = -2x + 42
x - (-2x + 42) = -3
x + 2x - 42 = -3
3x - 42 = -3
3x = 39
x = 13
y = -2(13) + 42
y = -26 + 42
y = 16
ANS : 13 and 16
2006-12-23 12:29:38
·
answer #1
·
answered by Sherman81 6
·
4⤊
0⤋
Let the numbers be x and y.
one# = y
another# = x
=> y + 2x = 42 [first equation]
now,
=> y - x = -3 [second euation]
solving by ...[subtraction method]
y + 2x = 42
y - x = -3
---------------
3x = 45
x = 45/3
x = 15
=> y = [ y + 2x = 42 ]
...... = [ y + 2(15) = 42 ]
...... = [ y + 30 = 42 ]
...... = [ y = 42 - 30]
=> y = 12
2006-12-24 04:56:09
·
answer #2
·
answered by Akshay 2
·
1⤊
2⤋
2x+y=42
x-y=-3
You need to solve for x and y
Multiply the second equation by -2:
2x+y=42
-2x+2y=6
========
3y=48
y=16
2x+16=42
2x=26
x=13
(13,16)
Check:
2(13)+16=42
26+16=42
42=42
13-16=-3
-3=-3
2006-12-25 02:47:27
·
answer #3
·
answered by Anonymous
·
2⤊
0⤋
Set up a system of equations:
2x+y=42
x-y=-3
Solve for x and y.
You should get 13 and 16.
2006-12-23 20:28:23
·
answer #4
·
answered by AibohphobiA 4
·
3⤊
0⤋
I read the problem differently.
Let a be the first number and b be the second number.
a + 2b = 42
a - b = -3
So a= b-3
Substitute into the first equation:
(b-3) +2b=42
3b-3=42
3b=45
b=15
Since a=b-3=15-3=12
So the numbers are 12 and 15.
2006-12-23 20:34:05
·
answer #5
·
answered by Professor Maddie 4
·
1⤊
2⤋
x + 2y = 42
x - y = -3
-x + y = 3
3y = 45
y = 15
x - 15 = -3
x = 12
Numbers are 12 and 15
2006-12-23 20:41:51
·
answer #6
·
answered by novadeath69 2
·
1⤊
2⤋
first number =12, second number=15
2006-12-23 20:41:20
·
answer #7
·
answered by Soren 1
·
1⤊
2⤋
x+2y=42
x-y=-3 subtract
3y=45
y=15
x-15=-3
x=12
numbers are 12 & 15
2006-12-23 20:59:40
·
answer #8
·
answered by mu_do_in 3
·
1⤊
2⤋